Hematological and inflammatory markers in Han Chinese patients with drug-free schizophrenia: relationship with symptom severity - Yang, Cheng; Tian, Yinghan; Yang, Xiaoxue; Liu, Lewei; Ling, Chen; Xia, Lei; Liu, Huanzhong (Frontiers in Immunology, 2024)
Background: There is a growing amount of evidence suggesting that immunity and inflammation play an important role in the pathophysiology of schizophrenia. In this study, we aimed to examine the relationship between hematological and inflammatory markers with symptom severity in Han Chinese patients with drug-free schizophrenia.Methods: This retrospective study was conducted at Chaohu Hospital of Anhui Medical University and data were extracted from the electronic medical record system over a 5-year period (May 2017 to April 2022), including participants' general and clinical information as well as Brief Psychiatric Rating Scale (BPRS) scores and hematological parameters.Results: A total of 2,899 patients with schizophrenia were identified through the initial search. After screening, 91 patients and 141 healthy controls (HCs) were included. The patients had a higher value of neutrophils/lymphocytes ratio (NLR), monocyte/lymphocyte ratio (MLR), and platelet/ lymphocyte ratio (PLR) than HCs (all P < 0.001). MLR was positively correlated with BPRS total score (r = 0.337, P = 0.001) and resistance subscale score (r = 0.350, P = 0.001). Binary logistic regression analyses revealed that severely ill was significantly associated with being male and a higher value of MLR (Natural Logaruthm, Ln) (all P < 0.05), and the receiver operating characteristic (ROC) analysis showed good performance of a regression model with an area under the curve (AUC) value of 0.787.Patients with drug-free schizophrenia have an unbalanced distribution of peripheral blood granulocytes, and elevated NLR, MLR and PLR. Patients with higher value of MLR tend to have more psychotic symptoms, especially those symptoms of hostility, uncooperativeness, and suspiciousness. Our study gives a preliminary indication that MLR is a potential predictor of disease severity in patients with drug-free schizophrenia.